2002
DOI: 10.4049/jimmunol.169.12.6928
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DP4, the Most Frequent HLA II Molecule, Defines a New Supertype of Peptide-Binding Specificity

Abstract: Among HLA-DP specificities, HLA-DP4 specificity involves at least two molecules, HLA-DPA1*0103/DPB1*0401 (DP401) and HLA-DPA1*0103/DPB1*0402 (DP402), which differ from each other by only three residues. Together, they are present worldwide at an allelic frequency of 20–60% and are the most abundant human HLA II alleles. Strikingly, the peptide-binding specificities of these molecules have never been investigated. Hence, in this study, we report the peptide-binding motifs of both molecules. We first set up a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
115
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(144 citation statements)
references
References 49 publications
26
115
2
1
Order By: Relevance
“…Further analysis of the hexon peptide reveals a motif consistent with the HLA DP4-binding motif described by Castelli et al 10 Comparison of PBMC responses to a panel of overlapping peptides and single residue mutations in the IFN-g ELISPOT assay identified Leu 914 and Phe 919 as the major anchors at P1 and P6, respectively. Competition studies confirmed that peptides with Ser substitutions at either P1 or P6 did not bind to HLA DP4.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Further analysis of the hexon peptide reveals a motif consistent with the HLA DP4-binding motif described by Castelli et al 10 Comparison of PBMC responses to a panel of overlapping peptides and single residue mutations in the IFN-g ELISPOT assay identified Leu 914 and Phe 919 as the major anchors at P1 and P6, respectively. Competition studies confirmed that peptides with Ser substitutions at either P1 or P6 did not bind to HLA DP4.…”
Section: Discussionsupporting
confidence: 73%
“…This data is consistent with the analysis of the model HLA DP4 peptide Oxy 271-287 : the P1 and P6 anchors were critical for peptide binding, whereas deletion of the minor P9 anchor did not eliminate binding. 10 Deletion of the hexon peptide Cterminal 6 residues, which includes the P6 and P9 anchors from both motifs, completely eliminated the PBMC response (H910-918). Additionally, PBMC did not recognize H916-925, a peptide with a deletion of the Nterminal 6 residues that deletes the motif 1 P1 anchor but retains the entire motif 2.…”
Section: Identification Of a Hla Dp4-binding Motifmentioning
confidence: 99%
“…Furthermore, grouping amino-acid polymorphisms at positions 36, 56, and 76 failed to define recognised supertypes, and were not associated with leukaemia (data not shown). Clustering of DP alleles into six supertypes based on amino acid dimorphisms at positions 84 (P1 pocket), 69 (P4 pocket), and 11 (P6 pocket) represents an expanded version of the scheme proposed by Castelli et al (2002) based on peptide binding, and a slightly modified version of the hierarchical clustering scheme proposed by Doytchinova and Flower (2005). We have provisionally denoted the six supertypes DP1 (GKD), DP2 (GEG), DP3 (LKD), DP4 (GKG), DP6 (LED), and DP8 (GED) since they broadly resemble those defined in the primed lymphocyte test (PLT) as DPw specificites (De Koster et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Since different alleles can have overlapping peptide-binding properties, depending on the number of PBP that they share (Southwood et al, 1998), this has permitted DR alleles with the same amino acid polymorphisms lining specific peptidebinding pockets to be clustered into supertypes Southwood et al, 1998;Doytchinova and Flower, 2005). Using a similar approach, Castelli et al (2002) defined three DP supertype clusters with shared amino acid residues in the P1 (b84) and P6 (b11) PBP. However, the P4 peptide-binding pocket, at position b69, also makes an important contribution to antibody and peptide-binding (Arroyo et al, 1995;Chicz et al, 1997), T-cell responses (Berretta et al, 2003;Diaz et al, 2003) and disease susceptibility (Potolicchio et al, 1999;Wang et al, 1999).…”
mentioning
confidence: 99%
“…10,11 Moreover, detailed analysis of HLA-DP4 peptide binding may facilitate future searches of novel tumour antigenic peptides restricted by this frequently occurring class II MHC allele. 12 Another favourable trait is the "degenerate" DR binding of certain antigenic peptides, i.e., various TA-derived antigenic peptides have been reported to bind to diverse HLA-DR molecules. 13,14 The identification of TA-derived epitopes presented by MHC class II molecules is complicated by the lack of effective screening methods.…”
Section: Tumour Antigensmentioning
confidence: 99%